Investigation of the genetic basis of antibiotic resistance in Mycobacterium tuberculosis - Evans, Joanna (Division of Medical Microbiology, 2014)
The emergence of antibiotic resistant strains of Mycobacterium tuberculosis, coupled with the time it takes to perform phenotypic drug susceptibility testing of this organism, makes the treatment of tuberculosis increasingly difficult. Several genotypic assays for the rapid detection of drug resistance in M. tuberculosis have been developed, but the sensitivity with which these assays identify resistance differs geographically. Additionally, the identification of phenotypically resistant isolates with no identifiable genotypic marker suggests that other factors, such as differential gene expression, may play a role in the development of drug resistance in M. tuberculosis. This investigation aims to both develop and evaluate rapid genotypic assays for the detection of resistance to both first- and second-line drugs in M. tuberculosis, and to investigate the role of alternative sigma factors in the progression to multidrug resistant M. tuberculosis.